Peculiarities of Conducting and Taxing the Business of Sole Proprietors (SPs) - HAMAN, Halyna; KORSUN , Inna (Ways to Improve Construction Efficiency, 2024)
The article examines the peculiarities of conducting business and taxation of sole proprietors (SPs) taking into account modern realities and further prospects of their effective activity. The opening of a record number of SPs for Ukraine, despite the war, is a manifestation of the stability of domestic business, in which a significant place is given to the role of women. The authors determined that the features of the organization of creation, management and closure of SPs in Ukraine include: quick registration through Diya; restriction of activity under certain types of NACE codes (gaming business, production of tobacco products, alcohol, precious metals, etc.); choice of taxation system (general or simplified system); simplified forms of accounting are provided; the use of accountants on the terms of outsourcing (without employment in the company’s staff); the use of modern software-based cash registers (PPO) as a replacement for traditional cash registers (RRO); simplified form of financial reporting; accounting calendar for reporting; the ability to quickly close a business through the Diya platform. The level of organization of accounting affects the effectiveness of ensuring the entire system of interests of users of financial reporting and the functioning of accounting at the enterprise, as well as its reliability, timeliness and effectiveness in general. The authors of the article indicate the importance of using modern PPO or "cash registers in smartphones", which is one of the important components of conducting business without fines for most SPs. An analysis of the dynamics of the use of modern PPO and RRO programs was carried out, in particular, the number of payments that were recorded under both systems during 2023 and the beginning of 2024. A comparative characteristic of the features of the use of PPO and RRO was given. The advantages and disadvantages of each type of cash register are determined. The tax regulation regarding fines, which are most often applied to business, is covered. The prospects for the activity of SPs in Ukraine in the near future were studied. It was found out, according to the draft Law of Ukraine No. 11416(d), that it is planned to make amendments and additions to the Tax Code of Ukraine in terms of increasing taxes for private enterprises, unification of some groups of the simplified taxation system, etc. The business prospects of SPs are indicated, taking into account the National Revenue Strategy until 2030.